2021
DOI: 10.1039/d1nj00231g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular level insights into the direct health impacts of some organic aerosol components

Abstract: Organic aerosols (OAs) comprise 20-90 w% of atmospheric aerosols. While they have some positive impacts (e.g. acting as precipitation nuclei), they can pose some negative impacts on human health. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 101 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…For example, black carbon aerosols can heat the atmosphere, evaporate cloud droplets to reduce cloud cover [11], create stable atmospheric stratification [12], weaken convection, and reduce rain showers. High concentrations of aerosol particles seriously affect human health [13][14][15]. A number of studies have shown that the incidence of cardiopulmonary disease is closely related to the content of particulate matter in polluted air [16][17][18], especially the inhalable fine particles, such as PM 2.5 , which can be inhaled into the lungs, attached to the alveoli, or entered into the blood circulation through the alveoli, posing a great threat to human health [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, black carbon aerosols can heat the atmosphere, evaporate cloud droplets to reduce cloud cover [11], create stable atmospheric stratification [12], weaken convection, and reduce rain showers. High concentrations of aerosol particles seriously affect human health [13][14][15]. A number of studies have shown that the incidence of cardiopulmonary disease is closely related to the content of particulate matter in polluted air [16][17][18], especially the inhalable fine particles, such as PM 2.5 , which can be inhaled into the lungs, attached to the alveoli, or entered into the blood circulation through the alveoli, posing a great threat to human health [19,20].…”
Section: Introductionmentioning
confidence: 99%